Transcriptomics and Antioxidant Analysis of Two Chinese Chestnut (Castanea mollissima BL.) Varieties Provides New Insights Into the Mechanisms of Resistance to Gall Wasp Dryocosmus kuriphilus Infestation - Zhu, Cancan; Wang, Wu; Chen, Yu; Zhao, Yuqiang; Zhang, Shijie; Shi, Fenghou; Khalil-Ur-Rehman, Muhammad; Nieuwenhuizen, Niels J. (Frontiers in Plant Science, 2022)
Chinese chestnut is a popular fruit tree with a high nutritional value of its nuts which can suffer from infestation by the chestnut gall wasp Dryocosmus kuriphilus (GWDK) that results in gall formation and resultant loss of production and profitability. The physiological and molecular mechanisms of GWDK resistance found in certain genotypes currently remains elusive. To gain new insights into this phenomenon, a series of RNA-Seq integrated with metabolomic profiling experiments were executed to investigated the chemical and transcriptional differences in response to GWDK infestation in two contrasting chestnut varieties grown in China (the susceptible ‘HongLi’-HL and the partially resistant ‘Shuhe_Wuyingli’-SW). Three time points were selected for comparison: The Initiation Stage (A), Growth Stage (B) and Maturation Stage (C). Results showed that concentrations of H2O2 and the activities of peroxidase (POD) and superoxide dismutase (SOD) enzyme were elevated in the resistant SW leaves compared to HL leaves at all three developmental stages, while catalase (CAT) and polyphenol oxidase (PPO) activities were mostly higher in HL leaves. RNA-Seq transcriptomic analyses of HL and SW leaves revealed that various metabolic pathways involved in GWDK stress responses, such as plant hormone signal transduction, MAPK signaling, as well as the peroxisome pathway, were enriched in the contrasting samples. Moreover, weighted gene coexpression network analysis (WGCNA) of differentially expressed genes in the POD pathway combined with transcription factors (TFs) indicated that the expression of TF members of bHLH, WRKY, NAC and MYB family positive correlated with peroxidase (POD) pathway gene expression. The TFs CmbHLH130 (EVM0032437), CmWRKY31 (EVM0017000), CmNAC50 (EVM0000033) and CmPHL12 (EVM0007330) were identified as putative transcription factors that participate in the regulation of insect-induced plant enzyme activities in chestnut, which may contribute to GWDK resistance in SW. Expression levels of 8 randomly DEGs were furthermore selected to perform qRT-PCR to validated the accuracy of the RNA-Seq-derived expression patterns. The present work will guide the functional analyses of further candidate genes and mechanisms important for GWDK resistance in chestnuts in the future as well as can help in identifying the master transcriptional regulators and important enzyme steps that support major insect defence pathways in chestnut.